Unmaking imperial Russia : Mykhailo Hrushevsky and the writing of Ukrainian history - Plokhy, Serhii, 1957- (University of Toronto Press, 2005)
"Hrushevsky took an active part in the work of Ukrainian scholarly, cultural, and political organizations and became the first head of the independent Ukrainian state in 1918. Serhii Plokhy's Unmaking Imperial Russia examines Hrushevsky's construction of a new historical paradigm that brought about the nationalization of the Ukrainian past and established Ukrainian history as a separate field of study. By showing how the 'all-Russian' historical paradigm was challenged by the Ukrainian national project, Plokhy provides the indispensable background for understanding the current state of relations between Ukraine and Russia."--Jacket